Mitigation of Natural Disasters as Efforts to Minimize Unwanted Impacts in Baleendah Sub-District, Bandung Regency, Indonesia - Yuyun Hidayat; Sukono Sukono; Kalfin Kalfin (International Journal of Research in Community Services, 2021)
The Flood disaster is a natural event, one of which is caused by overflowing rivers. This disaster often occurs in the Majalaya area, Bandung Regency. Geographical conditions close to the Citarum River flow and the plains lower than the surrounding area causes this area to be flooded especially during the rainy season. Through the Community Service Program with the topic "training and simulation of natural disaster mitigation as an effort to minimize unwanted impacts in Majalaya sub-district" aims to increase the knowledge of the surrounding community regarding the impact of flood disasters and efforts to reduce the impact through mitigation efforts. This activity is aimed at 8th graders of SMP Negeri 1 Majalaya by using the presentation method using WhatsApp group media. This activity begins with giving questionnaire I which functions as a pre-test and ends with questionnaire II which functions as a post-test. The questionnaire was given at the beginning and at the end to see to what extent the material gave influence and new knowledge to students of SMP Negeri 1 Majalaya. The results of the questionnaire show that prior to counseling on flood disaster mitigation, the sample was categorized as having good knowledge of 87% and having poor knowledge of 13%. After counseling about flood disaster mitigation using PowerPoint media and games there was an increase in knowledge, the sample with good knowledge was 98% and those with poor knowledge were 2%. Based on the results of the pre-test and post-test, this activity proved successful in increasing the knowledge of SMP Negeri 1 Majalaya regarding flood mitigation.